Pengaruh Pemberian Aromatherapi Jahe Terhadap Mual Muntah Pada Ibu Hamil Trimester I - Herni Kurnia (Poltekkes Kemenkes Bandung, 2019)
ABSTRACT: Pregnancy is the growth and development of the fetus starting from conception and ending until the beginning of labor. Pregnancy causes physiological changes that occur throughout the organ system, most of the changes in the mother's body are mostly caused by hormonal work. Changes that occur in pregnant women can cause discomfort in pregnancy, one of which is nausea and vomiting. Based on the results of the study 50-90% of pregnant women experience nausea in the first trimester. Handling vomiting nausea during pregnancy can be done through pharmacological and non-pharmacological actions. One of the non-pharmacological therapies is Aromatherapy Ginger. The purpose of this study was to determine the effect of Ginger Aromatherapy on Nausea Vomiting in Trimester I Pregnant Women. The research design is quasy experiment, with the type of pre-post test control group design. This research was conducted at Purbaratu Health Center, Tasikmalaya city 2019. Samples were selected by purposive sampling and obtained a sample of 36 respondents. The results of the study Regarding the number of respondents who did not need to throw nausea after being given ginger aromatherapy as many as 12 people (66.7%) and the Mann Whitney test results on the study group obtained a p value <0.05 thus associated with the help of ginger aromatherapy for nausea shooting in mothers 1st trimester of pregnancy in the Work Area of ​​Purbaratu Health Center, Tasikmalaya City.